Beneath these cursed stars eaudiobook - Ryan, Lexi (These Hollow Vows, 2024)
#1 New York Times bestselling author Lexi Ryan brings us the first book in a new romantic fantasy set in the enchanting world of These Hollow Vows. When a human princess armed with death's kiss allies with a fae shifter on the run, their mission to assassinate an evil king collides with a fatal prophecy. Princess Jasalyn has a secret. Armed with an enchanted ring that gives her death's kiss, Jas has been sneaking away from the palace at night to assassinate her enemies. Shape-shifter Felicity needs a miracle. Fated to kill her magical father, she's been using her unique ability to evade a fatal prophecy. When rumors of evil king Mordeus's resurrection spread through the shadow court, Jasalyn decides to end him once and for all. Felicity agrees to take the form of the princess, allowing Jas to covertly hunt Mordeus—and starting Felicity on the path that could finally take her home. While Jasalyn teams up with the charming and handsome Kendrick, Felicity sets out to get closer to the Wild Fae king, Misha. Kendrick helps Jasalyn feel something other than anger for the first time in three years, and Misha makes Felicity wish for a world where she's free to be her true self. Soon, the girls' missions are at risk right alongside their hearts. The future of the human and fae realms hangs in the balance as fates intertwine. Between perilous tasks, grim secrets, and forbidden romances, Jasalyn and Felicity find that perhaps their stars are the most cursed of all.